2017
DOI: 10.1111/jdv.14188
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of phenotype, comorbidities, therapy and adverse events between psoriatic patients with and without psoriatic arthritis. Biobadaderm registry

Abstract: Given the differences between patients with psoriasis alone or with psoriasis associated with PsA, patients with psoriasis and PsA should be followed and managed more closely and with specific attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
3
0
2
Order By: Relevance
“…Several studies have reported increased risk of infections with biologic use in patients with psoriasis [2, 47] and rheumatoid arthritis (RA) [2, 812]. Likewise, patients with PsA have been reported to have an increased risk of comorbidities and adverse events (AEs), including serious infections (SIs), compared with patients with psoriasis [13, 14]. Many investigators question whether the increased risk for AEs is due to the underlying inflammatory nature of psoriatic disease itself, or to the therapies used to treat the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported increased risk of infections with biologic use in patients with psoriasis [2, 47] and rheumatoid arthritis (RA) [2, 812]. Likewise, patients with PsA have been reported to have an increased risk of comorbidities and adverse events (AEs), including serious infections (SIs), compared with patients with psoriasis [13, 14]. Many investigators question whether the increased risk for AEs is due to the underlying inflammatory nature of psoriatic disease itself, or to the therapies used to treat the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with psoriasis often have other comorbidities such as dyslipidemia, type 2 diabetes, obesity or metabolic syndrome, though one of the most common diseases is arterial hypertension [25,[34][35][36][37]. In this study, arterial hypertension was diagnosed for 40.5% of all subjects with severe psoriasis.…”
Section: Comorbiditiesmentioning
confidence: 71%
“…Further, patients with psoriasis or PsA are not necessarily similar; only 20-30% of patients with psoriasis develop PsA 22 . A previous study comparing patients with psoriasis without arthritis to those with psoriasis and PsA found more comorbidities and combined systemic treatment such as biologic drugs in the PsA group 23 . Given that in this study the investigators could not differentiate between psoriasis and PsA using ICD-9 codes, it is possible that patients with mild psoriasis without IA were a substantial part of the SpA group.…”
mentioning
confidence: 84%